Classifying Countries According to Their Export Competitiveness: The Position of Turkey as An Emerging Economy - Taşkın Dirsehan (Online Academic Journal of Information Technology, 2015)
Country classification is useful from both firms’ and countries’ side. Firms may use the classification to decide which countries to operate in and countries may use it for their development. As there is evidence that the development of a country relates on export competitiveness, this study tries to reveal specifically sector groups’ relationships with it and how the countries can be classified according to the country export competitiveness. As a result, Turkey’s position is evaluated and the importance of technology advancement is discussed.